2018
DOI: 10.1016/j.gca.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity of oxalate surface complexes on lepidocrocite derived from infrared spectroscopy, DFT-calculations, adsorption, dissolution and photochemical experiments

Abstract: Oxalate, together with other ligands, plays an important role in the dissolution of iron(hdyr)oxides and the bio-availability of iron. The formation and properties of oxalate surface complexes on lepidocrocite were studied with a combination of infrared spectroscopy (IR), density functional theory (DFT) calculations, dissolution, and photochemical experiments. IR spectra measured as a function of time, concentration, and pH (50-200 µM oxalate, pH 3-7) showed that several surface complexes are formed at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…Di-carboxylic But2/4 (succinic) and Hex2/6 (adipic), however, may adsorb via just one of their carboxyl groups, possibly due to steric constraint on formation of a bidentate mononuclear structure 54 , while tri-carboxylic Pro3/6 might adsorb via two carboxyl groups, although the exact adsorption configuration is unknown 56 . Both mono-and polycarboxylic acids may also form outer-sphere complexes (particularly at basic pH) 57,58 . Since our π* C=O carboxyl carbon peak shift is constant for the mono-(−0.1 ± 0.0 eV), di-(−0.2 ± 0.04 eV) and tri-carboxylic acids (−0.4 ± 0.0 eV) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Di-carboxylic But2/4 (succinic) and Hex2/6 (adipic), however, may adsorb via just one of their carboxyl groups, possibly due to steric constraint on formation of a bidentate mononuclear structure 54 , while tri-carboxylic Pro3/6 might adsorb via two carboxyl groups, although the exact adsorption configuration is unknown 56 . Both mono-and polycarboxylic acids may also form outer-sphere complexes (particularly at basic pH) 57,58 . Since our π* C=O carboxyl carbon peak shift is constant for the mono-(−0.1 ± 0.0 eV), di-(−0.2 ± 0.04 eV) and tri-carboxylic acids (−0.4 ± 0.0 eV) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kubicki et al (2017) studied the adsorption of oxalate on goethite and the mechanism of reductive dissolution using DFT calculations, and they showed that oxalate is most stable as a bidentate mononuclear complex. Borowski et al (2018) studied oxalate complexation on lepidocrocite using ATR-FTIR spectroscopy and DFT calculations by changing the pH and surface loading, and MM and BM complexes were identified. The increase in pH leads to a decrease in the content of the BM complex, and UV light causes photolysis of the BM complex compared to the MM or outer-sphere complex.…”
Section: Structural Configuration Of Organic Acidsmentioning
confidence: 99%
“…For oxalate, detailed DFT calculations allowed us to draw conclusions about the structures of these different surface complexes. 49 DFT calculations with the larger ligand EDTA in the presence of Fe(II) are computationally more demanding and were not attempted in this study.…”
Section: Lp Dissolution Monitored With Atr-ftirmentioning
confidence: 99%